DESIGN AND IMPLEMENTATION OF PERSONNEL TRACKING AND COMBAT VEHICLE BASED ON MICROCONTROLLERS - Yudi Efendi; Petrus Gunawan; Eko Kuncoro (Merdeka Malang University, 2020)
Abstract - Training is a necessity to achieve a level of professionalism in carrying out the main tasks of the Indonesian National Army (TNI) to safeguard the Sovereign State of the Republic of Indonesia (NKRI). With the development of technology, the flow of information that is well ordered, fast and interconnected is very important in a command control function that is packaged into a battle management. This study aims to create a system that can provide information support to the Unit Commander in giving command instructions to his troops. The information includes coordinates, altitude, balance, speed and compass, and is integrated with LCO (Lambert Conical Orthomophic) Map which can be integrated into Google Satellites so that tracking and monitoring of troops will be easier. Based on the results of tests that have been carried out it can be analyzed that the value of the error presentation of the actual measurements with measurements on the program is not too large. The comparison obtained is less than 2% so that by using the system it is expected that each unit can operate optimally and efficiently.